A Comparison of Petri Net Semantics under the Collective Token Philosophy - Bruni, Roberto; Meseguer, José; Montanari, Ugo; Sassone, Vladimiro (BRICS Report Series, 1998)
In recent years, several semantics for place/transition Petri nets have been proposed that adopt the collective token philosophy. We investigate distinctions and similarities between three such models, namely configuration structures, concurrent transition systems, and (strictly) symmetric (strict) monoidal categories. We use the notion of adjunction to express each connection. We also present a purely logical description of the collective token interpretation of net behaviours in terms of theories and theory morphisms in partial membership equational logic.